Gross Morphological and Biometrical Studies on the Male Accessory Genital - Nissar, Shazia; Suri, Shalini; Sarma, Kamal; Doley, P J (Indian Journal of Veterinary Anatomy, 2012)
The study conducted on six adult boars revealed that the seminal vesicles were large, lobulated, three sided, pyramidal masses and pale pink in colour. The left seminal vesicle was comparatively larger and heavier than the right one. The corpus prostate was distinct and pars-disseminate surrounded the lumen of pelvic urethra. The bulbourethral glands were very large, dense and cylindrical masses. The right bulbourethral gland measured more than the left one in length and weight.